KARAKTERISTIK PENGGUNA SEPEDA LIPAT TERHADAP PEMILIHAN MODA TRANSPORTASI DI KOTA PALEMBANG - Praditya, Norca; Rahmadona, Efrilia; Sudarmadji, Sudarmadji; Pratama, Ade Surya (Universitas Muhammadiyah Palembang, 2020)
Sustainable Transportation is one of the embodiment of sustainable development, sustainable development puts forward the concept of eco-friendly urban, where the concept aims to balance the increasingly rapid development activities with an eco- friendly transportation system that is integrated with other modes of transportation, particularly the public transportation. Through this research, it is expected that it will become a reference for planning the development of bicycle routes and lanes in the city of Palembang. The research method used was a quantitative descriptive approach, data collection techniques conducted through a questionnaire survey, the total population was 966 cyclists, the sample taken for respondents with the Slovin formula was 478 respondents. The sampling technique used was simple random sampling, the results of data processing will be illustrated in tables and diagrams and calculations for the study of bicycle route lane using a matrix of origin and destination. Based on the questionnaire data obtained, from the survey results of 478 respondents, the percentage of cyclist was predominantly male and it was 91%, based on the analysis of activity patterns of folding cyclists, it indicated that the use of bicycle was 77% and it intended to the purpose of sports trips, 8% was for the purpose of recreation, 6% was for the purpose of daily activities, 5% was for the purpose of social travel, and the last 4% was for work purposes. 20% of folding cyclists were aimed to the short trips ? 10 km, while the use of bicycles for medium distances, which was around 10 km to 40 km, with the largest percentages was 38% and 32%. 68% of folding cyclist stated that the bicycle mode was the most economical mode of transportation. Dealing with the analysis for the opportunity to develop special bicycle routes and lanes, bicycle users were enthusiastic to obtain supporting facilities in the form of special bicycle lanes, 97% of cyclists agreed that a special bicycle lane must be provided. The selection of roads for bicycle routes was based on the calculation of the origin and destination matrix for the cyclists, the districts of the most potential cyclists were selected as starting and ending points for the bicycle route. Thus, 2 alternatives were selected for the special bicycle route. Key Words: sustainable transportation, characteristics, bicycle route, bicycle lane